Clinical Implications of Basic Research: Exploring the Transformative Potential of Spatial 'Omics in Uro-oncology - Figiel, Sandy; Bates, Anthony; Braun, David A.; Eapen, Renu; Eckstein, Markus; Manley, Brandon J.; Milowsky, Matthew I.; Mitchell, Tom J.; Bryant, Richard J.; Sfakianos, John P.; Lamb, Alastair D. (European Urology, 2024)
New spatial molecular technologies are poised to transform our understanding and treatment of urological cancers. By mapping the spatial molecular architecture of tumours, these platforms uncover the complex heterogeneity within and around individual malignancies, offering novel insights into disease development, progression, diagnosis, and treatment. They enable tracking of clonal phylogenetics in situ and immune-cell interactions in the tumour microenvironment. A whole transcriptome/genome/proteome-level spatial analysis is hypothesis generating, particularly in the areas of risk stratification and precision medicine. Current challenges include reagent costs, harmonisation of protocols, and computational demands. Nonetheless, the evolving landscape of the technology and evolving machine learning applications have the potential to overcome these barriers, pushing towards a future of personalised cancer therapy, leveraging detailed spatial cellular and molecular data. Patient summary: Tumours are complex and contain many different components. Although we have been able to observe some of these differences visually under the microscope, until recently, we have not been able to observe the genetic changes that underpin cancer development. Scientists are now able to explore molecular/genetic differences using approaches such as “spatial transcriptomics” and “spatial proteomics”, which allow them to see genetic and cellular variation across a region of normal and cancerous tissue without destroying the tissue architecture. Currently, these technologies are limited by high associated costs, and a need for powerful and complex computational analysis workflows. Future advancements and results through these new technologies may assist patients and their doctors as they make decisions about treating their cancer.
CRIS-Team Scopus Importer:2024-09-13
Keywords: Genomics; Proteomics; Transcriptomics; Urological cancer